Digital divide: Barriers to accessing online government services in Canada - Vikkram Singh; Joshua Chobotaru (Administrative Sciences, 2022)
This study investigates the digital divide in Canada related to access to online government services. Since digital equity can have welfare implications, it is an important area to explore. We use a bivariate logit model to estimate the determinants of access to e-government services. The results show significant disadvantages for females, those who cannot speak official languages, those living in rural areas and those in the lower quantiles of household income. Public policy measures such as infrastructure development in rural areas, improvement in digital equity and streamlining of e-government access can help address this issue.
Keywords: 350; COVID-19; e-government; Canada; digital divide; logistics